2020
DOI: 10.2147/clep.s271275
|View full text |Cite
|
Sign up to set email alerts
|

<p>Blood Transfusion and the Risk of Cancer in the US Population: Is There an Association?</p>

Abstract: We aimed to test if blood transfusion is a risk factor for the prevalence of cancer. Patients and Methods: We conducted secondary analyses using the NHANES database from 1999 to 2016. We included all individuals who received a blood transfusion with known cancer comorbidity (diseased or not). We used univariate logistic regression to identify any possible association between history of blood transfusion and the prevalence of cancer with adjustment for different co-founders was done. Regression results were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Logistic regression was used to identify any possible association between activity-related behavior participation and stroke incidence among the matched sample. 14 Regression results were expressed as odds ratios (ORs) and 95% confidence interval (95% CI). P-value <0.05 was considered significant for all statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression was used to identify any possible association between activity-related behavior participation and stroke incidence among the matched sample. 14 Regression results were expressed as odds ratios (ORs) and 95% confidence interval (95% CI). P-value <0.05 was considered significant for all statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no known cases of transfusion-associated viral hepatitis reported in the UK shortly after transfusion since 2005 (11). Recent studies have found no association between blood transfusion and the risk of cancer (12). However, blood transfusion is an important risk factor for postoperative complications in cancer patients (13).…”
Section: Introductionmentioning
confidence: 99%